Effect of Leadership Styles on Teachers’ Attitudes towards Teaching in Public Sector Universities - Saima Rehman; Dr. Syed Afzal Shah (International Journal of Business and Economic Affairs, 2022)
This study was conducted to investigate the effect of leadership styles on teachers’ attitudes towards teaching in public sector universities. The study was also based on quantitative approach as variable were measured with numbers and analyzed with statistical procedures. All the public universities of Hazara division and all the faculty members from these public universities were constituted the population of the study. The data was collected through self-developed questionnaires. One questionnaire was related to leadership styles and the other was related to attitude of teachers towards teaching. A sample of 250 faculty members (both male and female) was selected from University of Haripur (UOH), Hazara University (HU) Mansehra, and Abbottabad University of Science and Technology (AUST). Stratified simple random sampling technique was used to collect data. Analysis of the result shows that leadership styles has significant positive effect on teachers’ attitude towards teaching. The conclusions were drawn from the finding and recommendations were made on the basis of finding and conclusion of study.